Adaptability evaluation model and experiment of full section SBM in deep strata based on AHP-fuzzy theory - Suqian Ni; Ying Xu; Peiyuan Chen; Jinjin Ge; Rongzhou Yang; Ziyi Yang; Guang Yang (Scientific Reports)
Abstract To delve into the adaptability of the full section SBM boring process during its inaugural application, this paper innovatively put forward an adaptability evaluation model for the SBM shaft boring within composite deep strata. This model is with the degree of adaptability T as the quantitative criterion. Initially, the evaluation index system of SBM boring adaptability is established. The determination of the adaptive standard for evaluation indexes and the calculation parameters of the model is based on a comprehensive approach that encompasses rock abrasion testing and extensive field investigations. Furthermore, based on the principle of AHP, the weight total ranking of SBM boring adaptability evaluation indexes is given under this method. Ultimately, fuzzy mathematics theory is introduced, and the fuzzy comprehensive evaluation and its verification is conducted. The results show that: the five factors that have the greatest influence on the adaptability of SBM boring in composite deep strata are, in order: I 3 > I 5 > I 4 > I 6 > I 11. Based on the adaptability evaluation model of SBM boring and by the principle of weighted average, the adaptability of the SBM boring process response is “strong adaptability”. Through the engineering case, the scientific rationality of the SBM adaptability evaluation method in the composite deep strata has been verified.